Evaluation of carcinoembryonic antigen‐related cell adhesion molecule 1 blood serum levels in women at high risk for preeclampsia. (25th November 2020) - Mach, Pawel; Andrikos, Dimitrios; Schmidt, Boerge; Gellhaus, Alexandra; Rusch, Peter; Birdir, Cahit; Andrikos, Argyrios; Schmitt, Verena; Kimmig, Rainer; Singer, Bernhard B.; Köninger, Angela
Abstract: Problem: The aim of this study was to evaluate the sCEACAM1 concentrations in serum from patients in the first trimester who have a high risk for developing PE during pregnancy. Method of the study: Carcinoembryonic antigen‐related cell adhesion molecule 1 (CEACAM1) levels were determined with ELISA. The patients ( n  = 109) were divided into two groups: patients who have a high risk of developing PE early‐onset and a control group. Patients who have a high risk of developing PE were then divided into two subgroups depending on PE development in third trimester of pregnancy: PE in third trimester versus no PE in third trimester. Results: sCEACAM1 concentrations in patients who were screened as having a high risk for developing PE were significantly higher than in healthy pregnant women in the first trimester ( p  = .03). The highest sCEACAM1 concentration was found in the high‐risk group with PE development compared to the control group ( p  = .004). Conclusion: Elevated sCEACAM1 blood serum levels in women with PE suggest that there is immune dysregulation in early pregnancy, which may be helpful in PE prediction and therapy.